Growth inhibition of Fusarium oxysporum f. sp. nicotianae by two in vitro poisoning methods with fungicides of different toxicological groups - Ceiro-Catasú, Wilson Geobel; Rueda-Puente, Edgar Omar; Rondón-Fonseca, Richard; Sosa-Sánchez, Oandis; Holguín-Peña, Ramón Jaime (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Wilt caused by Fusarium oxysporum f. sp. nicotianae is one of the most important fungal diseases in tobacco cultivation, being also one of the most difficult to control. The in vitro effectiveness of two poisoning methods was evaluated; sensi-disc (SD) and medium dilution (DMC) to determine the inhibitory effect of four fungicides of different toxicological groups on F. oxysporum isolated from tobacco in different regions of the province of Granma, Cuba. A differential response was observed in the susceptibility levels of all strains tested, regardless of the method of poisoning. The DMC method was more efficient than the SD, observing increases from 4.37 % (S) to 45.57 % (Ip+Pr) with respect to the SD. The highest inhibition values were observed in DMC with mancozeb (100 %), Tz+Az (79.74 %), and Ip+Pr (96.9 %). The greatest effectiveness in sporulation inhibition was with mancozeb by the SD method (0 %). The in vitro inhibitory effect of the fungicides evaluated (alone or in combination) is indicative of the fungicidal effect on the fungus under study and establishes the importance of inhibition methods for the study of fungicides used in management programs of diseases caused by Fusarium spp., in the tobacco growing areas of Cuba and other parts of the world.